Image and misreporting - Mara Ewers; Florian Zimmermann (Institute for the Study of Labor (IZA), 2012)
In this paper we ask if reports of private information about skills, abilities or achievements are affected by image concerns. We develop a simple model that illustrates how image utility can lead to misreporting of private information in contexts where truthful reports maximize monetary outcomes. In addition, we test the model's predictions in a controlled lab experiment. In the experiment, all subjects go through a series of quiz questions and subsequently report a performance measure. We vary if reports are made to an audience or not and find evidence for image effects. In the audience treatment, stated reports are significantly higher than in the private treatment. This suggests that overconfident appearance might be a consequence of social approval seeking. We also find that men state higher self-assessments than women. This gender difference seems to be driven by men responding more strongly to the presence of an audience.
urn:nbn:de:101:1-201207125585
Keywords: C91; D03; D82; 330; image concerns; self-assessment; overconfidence; experiment